2016
DOI: 10.17554/j.issn.2311-5106.2016.03.172
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Plane Malalignment in Paediatric Supracondylar Fractures of the Distal Humerus: A Review of the Literature

Abstract: AIM: Sagittal plane malalignment in supracondylar fractures of the humerus is thought to remodel well and be of doubtful functional significance. Consequently it has been given little attention. Our aim was to review the contemporary literature for consensus about the optimal radiographic method to assess sagittal plane alignment, define acceptable limits of reduction in this plane and assess the functional consequences of the ensuing hyperextension deformity. METHODS: A search of MEDLINE(Ovid), PubMed, EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The humerocapitellar angle of our patients on the operated side, average Gartland type IIA: 43.06 ± 2.19; type IIB: 40.34 ± 2.22; type III: 42.32 ± 2.81; and type IV: 40.63 ± 3.52 degrees. The average results for all fracture types were within the normal range [ 17 ]. A statistically significant difference was found between type IIA and type IV (p=0.032).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The humerocapitellar angle of our patients on the operated side, average Gartland type IIA: 43.06 ± 2.19; type IIB: 40.34 ± 2.22; type III: 42.32 ± 2.81; and type IV: 40.63 ± 3.52 degrees. The average results for all fracture types were within the normal range [ 17 ]. A statistically significant difference was found between type IIA and type IV (p=0.032).…”
Section: Discussionmentioning
confidence: 99%
“…Our distribution was found to be similar to the distribution in the study by Silverstein et al [ 19 ]. There is limited literature regarding the long-term functional consequences of sagittal plane deformity in pediatric supracondylar fractures [ 17 , 20 ]. In their study, Silverstein et al did not find a significant relationship between the degree of sagittal deformity and joint range of motion and humerocapitellar angle [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several literature reviews have suggested that sagittal plane alignment may play an important role in elbow flexion and ROM [15,16]. It has been hypothesized that inadequate reductions of supracondylar fractures may result in loss of elbow flexion [14,17].…”
Section: Discussionmentioning
confidence: 99%
“…The distal humeral segment occasionally remains posteriorly displaced and or malrotated following CRPP. There is limited literature pertaining to the long-term functional significance of sagittal and axial plane deformity in pinned supracondylar fractures [13][14][15][16][17], and none describe the significance of an anterior osseous fragment that is often created. In the current study, we attempted to determine the relationship between quality of reduction in the sagittal and axial planes, osseous resorption and correlation to ROM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and systematic reviews have been conducted to provide clarification on optimal pinning of supracondylar fractures, ranging from biomechanical analysis of configuration (8)(9)(10)(11)(12), entry point (13,14), pin size (11,13,15), number of pins (13,16,17), pin separation at the fracture site (8,18,19), and clinical outcome (4)(5)(6)20,21). The propensity for children to remodel mild deformities resulting from loss of position (22,23) and the frequent use of cast immobilization post fixation (24) may allow the use of pin configurations with diminished stability.…”
Section: Introductionmentioning
confidence: 99%